Effects of Fish Oil Supplementation on Cardiometabolic Risk Factors in Overweight or Obese Children and Adolescents: A Meta-Analysis of Randomized Controlled Trials - Wu, Shaojing; Zhu, Chunhong; Wang, Zhen; Wang, Shumei; Yuan, Pengfei; Song, Tao; Hou, Xiaoli; Lei, Zhixian (Frontiers in Pediatrics, 2021)
Background: Influences of fish oil supplementation on body weight and other cardiometabolic factors in overweight or obese children and adolescents remain not fully understood. We performed a systematic review and meta-analysis of randomized controlled trials (RCTs) to evaluate the role of fish oil for these children. Methods: Relevant studies were obtained by search of PubMed, Embase, and Cochrane's Library databases. A random-effect model, which incorporates the potential heterogeneity of the included studies, was used to pool the results. Results: Twelve RCTs including 1,028 overweight or obese children and adolescents were included. Compared to control, fish oil supplementation significantly reduced body mass index [BMI, mean difference (MD): −0.96 kg/m2, 95% confidence interval (CI): −1.69 to −0.23, P = 0.01] but did not significantly reduce body weight or waist circumference (P = 0.68 and 0.76). Moreover, fish oil supplementation significantly reduced serum triglyceride (MD: −0.24 mmol/L, 95% CI: −0.40 to −0.08, P = 0.004) but did not significantly affect serum total cholesterol and high-density or low-density lipoprotein cholesterol (P = 0.83, 0.42, and 0.31, respectively). Additionally, fish oil supplementation significantly lowered systolic blood pressure (SBP, MD: −2.46 mmHg, 95% CI: −4.93 to −0.01, P = 0.04) but did not significantly change diastolic blood pressure (P = 0.22). Supplementation with fish oil did not significantly affect fasting plasma glucose (P = 0.33). Conclusions: In overweight or obese children and adolescents, supplementation with fish oil could reduce BMI, decrease serum triglyceride, and lower SBP, while serum cholesterol and fasting glucose may not be significantly affected.